Білівський монастир як перспективний центр релігійно-паломницького туризму в Рівненській області - Сергійчук, Андрій Юрійович; Serhiichuk, A. Y. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Визначено історичні передумови виникнення Білівського монастиря. Проаналізовано особливості функціонування монастиря на різних часових проміжках. З’ясовано чинники розвитку обителі. Досліджено перспективи Білівського монастиря з погляду розвитку релігійно-паломницького туризму. The historical preconditions of the Bilivski Convent emerging have been examined. The functioning of the convent at different time intervals has been analyzed. The factors of the monastery evolution have been explored. The article studies Bilivski Convent from the perspective of the religious pilgrimage tourism development.
Bilivski Convent as a Perspective Religious and Pilgrimage Tourism Center in Rivne Region
Keywords: релігійно-паломницький туризм; Білівський монастир; Рівненська область; religious pilgrimage tourism; Bilivski Convent; Rivne region